The changing value of employment and its implications - Davide Alonzo; Giovanni Gallipoli (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
We characterize the employment value of different worker-occupation matches and estimate the substitutability of match-specific inputs in production. In an equilibrium model of the U.S. labor market, we examine the responses of employment and wages to shifts in technology and match values. Earnings are mainly driven by technology while match value heterogeneity influences the distribution of workers across occupations. The model delivers measures of rents and compensating differentials. After 1980, employment rents increased for educated workers but stagnated for others. Compensating differentials have risen on average, particularly in occupations where worker mobility has grown.
Keywords: D51; D58; J2; J3; J62; 330; employment; wages; equilibrium; technological change; heterogeneity; occupations